The influence of masculinity and femininity in responses to sex appeal advertising. Issue 4 (1st October 2016) - Lee, Seung Yeon; Lee, Seunghee
Abstract: This study examined the influence of gender identity on the effects of sex appeal advertising using a two (low/high nudity level of sex appeal) by two (male/female model) between-group factorial design. The results of this study are as follows. Firstly, both males and females strongly favored sex appeal advertisements (ads) with more, rather than less nudity. Secondly, whereas male respondents were more attracted to opposite sex (female) models than same sex models in sex appeal ads, female respondents were not influenced by the model's sex. Thirdly, male respondents reacted differently to sex appeal ads given their gender identity. A significant difference was found between the androgynous and the feminine groups; androgynous males showed the most positive attitude toward sex appeal ads and feminine males showed the least positive attitude. Finally, both male and female respondents' attitudes toward sex appeal advertising exhibited a significant interaction effect between gender identity and the model's sex. Both androgynous males and females showed more positive attitudes toward opposite sex models, whereas feminine males and females showed more positive attitudes toward models of the same sex as their own.